Integrating spatial and single-cell transcriptomes reveals the role of COL1A2(+) MMP1(+/-) cancer-associated fibroblasts in ER-positive breast cancer - Zhi-Hao Yu; Huan-Ling Xu; Shuo Wang; Ying-Xi Li; Gui-Xin Wang; Yao Tian; Zhao-Hui Chen; Wen-Bin Song; Long He; Xin Wang; Xu-Chen Cao; Yue Yu (Cancer Cell International)
Abstract Cancer-associated fibroblasts (CAFs) are highly heterogeneous cells and important components of the breast tumor microenvironment (TME). However, their role and clinical value in ER-positive breast cancer have not been fully clarified. Our study aims to comprehensively characterize the heterogeneity, potential biological functions, and molecular mechanisms of CAFs in ER-positive breast cancer within the tumor microenvironment using multi-omics data, to provide new strategies for the diagnosis and treatment of ER-positive breast cancer patients. In this study, we found that COL1A2(+) MMP1(+) and COL1A2(+) MMP1(-) CAFs were associated with unfavorable prognosis. The dynamic evolution and cell-cell communications of CAFs were analyzed, revealing that COL1A2(+) MMP1(+/-) CAFs show extensive crosstalk with tumor-associated macrophages (TAMs), contributing to an immunosuppressive TME. Moreover, the somatic mutation of TP53 may be a potential indicator for evaluating the infiltration of COL1A2(+) MMP1(+/-) CAFs. Finally, an MRI-based radiomic model was constructed to estimate the abundance of these CAFs. In conclusion, our findings provide a theoretical basis for targeting CAFs and offer a noninvasive approach to evaluate the infiltration level of COL1A2(+) MMP1(+/-) CAFs.